Effects of feeding a spray-dried multivalent polyclonal antibody preparation on feedlot performance, feeding behavior, carcass characteristics, rumenitis, and blood gas profile of Brangus and Nellore yearling bulls - Millen, D. D. [UNESP]; Pacheco, R. D.L.; DiLorenzo, N.; Martins, C. L. [UNESP]; Marino, C. T.; Bastos, J. P.S.T. [UNESP]; Mariani, T. M. [UNESP]; Barducci, R. S. [UNESP]; Sarti, L. M.N. [UNESP]; DiCostanzo, A.; Rodrigues, P. H.M.; Arrigoni, M. D.B. [UNESP] (Oxford University Press (OUP), 2015)
The objective of this study was to evaluate the effects of replacing monensin (MON) with a spray-dried multivalent polyclonal antibody preparation (PAP) against several ruminal microorganisms on feedlot performance, carcass characteristics, feeding behavior, blood gas profile, and the rumenitis incidence of Brangus and Nellore yearling bulls. The study was designed as a completely randomized design with a 2 × 2 factorial arrangement, replicated 6 times (4 bulls per pen and a total of 24 pens), in which bulls (n = 48) of each biotype were fed diets containing either MON fed at 300 mg/d or PAP fed at 3 g/d. No significant feed additive main effects were observed for ADG (P = 0.27), G:F (P = 0.28), HCW (P = 0.99), or dressing percentage (P = 0.80). However, bulls receiving PAP had greater DMI (P = 0.02) and larger (P = 0.02) final LM area as well as greater (P < 0.01) blood concentrations of bicarbonate and base excess in the extracellular fluid than bulls receiving MON. Brangus bulls had greater (P < 0.01) ADG and DMI expressed in kilograms, final BW, heavier HCW, and larger initial and final LM area than Nellore bulls. However, Nellore bulls had greater daily DMI fluctuation (P < 0.01), expressed as a percentage, and greater incidence of rumenitis (P = 0.05) than Brangus bulls. In addition, Brangus bulls had greater (P < 0.01) DMI per meal and also presented lower (P < 0.01) DM and NDF rumination rates when compared with Nellore bulls. Significant interactions (P < 0.05) between biotype and feed additive were observed for SFA, unsaturated fatty acids (UFA), MUFA, and PUFA concentrations in adipose tissues. When Nellore bulls were fed PAP, fat had greater (P < 0.05) SFA and PUFA contents but less (P < 0.01) UFA and MUFA than Nellore bulls receiving MON. For Brangus bulls, MON led to greater (P < 0.05) SFA and PUFA and less (P < 0.05) UFA and MUFA than Brangus bulls fed PAP. Feeding a spraydried PAP led to similar feedlot performance compared with that when feeding MON. Spray-dried PAP might provide a new technology alternative to ionophores.
Keywords: Brangus; Feedlot; Monensin; Nellore; Polyclonal antibody